Adolescent Medicine : a Handbook for Primary Care. - Strasburger, Victor C. (Wolters Kluwer Health, 2011)
Designed for quick reference in a busy office, this handbook is a concise, practical guide to everyday clinical problems in adolescent medicine. This ready-reference manual is written by noted experts to provide immediate, authoritative answers to questions about common medical and behavioral problems in teenagers. Numerous tables, bulleted lists, and charts help practitioners find information quickly, and a formulary offers guidance in prescribing for teenagers. Coverage includes every important topic in adolescent gynecology and up-to-date strategies for evaluating and treating obese teenage.